Lignocellulosic biomass as renewable feedstock for biodegradable and recyclable plastics production: A sustainable approach - Raj, Tirath; Chandrasekhar, K.; Naresh Kumar, A.; Kim, Sang-Hyoun (Renewable & sustainable energy reviews, 2022)
Rapid increment in fossil-derived single-use plastic disposal has led to human-made plastic mountains and leading to ecological imbalance. Therefore, the development of alternative environmentally friendly, biodegradable, and biobased plastics using lignocellulosic biomass renders sustainability. Lignocellulosic biomass offers an unprecedented opportunity to produce renewable fuels, chemicals, and materials for the replacement of fossils-based derivatives. The present review comprehensively delineates the potential of lignocellulosic biomass to produce biodegradable and recyclable plastics and plastic composites. Initially, various available pretreatment methods for the deconstruction of natural recalcitrance for fuel and chemical production are summarized, along with the challenges and scope of the integrated biorefinery approach. Energy chemicals such as ethanol, hydrogen produced under biorefinery approach may serve as precursor for bioplastics productions for sustainable bio future. Recyclable and biodegradable polymers such as polyglycolic acid, polyhydroxyalkanoates, polylactic acid, polybutylene succinate, polyvinyl alcohol, biobased polyethylene, biobased polyethylene terephthalate and cellulose acetate have been critically reviewed. Furthermore, the limitations, hurdles, and future scope of commercially available biorefinery industries are deliberated. Thus, technical development and integration in current biorefinery could promote the economical production of biobased biodegradable and recyclable plastics, simultaneously addressing waste biomass utilization constraints. [Display omitted] •Lignocellulosic biomass (LCB) is a potential renewable feedstock for biopolymer.•Low-cost and efficient pretreatment is essential to overcome the recalcitrance.•LCB-derived polymer is either biodegradable (e.g., PHA) or recyclable (e.g., Bio-PE).•Biopolymer can be reinforced with cellulose, lignin, graphene and natural fibers.•Integration with biofuel production is recommended for economics and sustainability.